Review of Marketing Ethics in Sharia Property Business Actors (Case Study on Sharia Property Business Actors in Maros Regency ) - Herman, Herman; Hamzah, Muh. Nasir; Sapa, Nasrullah Bin (Universitas Muhammadiyah Makassar, 2024)
In Islam, ethics serves as the guiding principle of distinguishing between right and wrong, based on the teachings of the Qur'an and the Sunnah (traditions of the Prophet Muhammad). Ethics holds significant importance in business endeavors, particularly in the context of marketing practices. This study aims to assess the alignment of marketing ethics among Sharia property entrepreneurs in Maros Regency with Islamic business ethics. Utilizing a qualitative research approach with a phenomenological perspective, data collection involved interviews, observations, and documentation. The findings indicate that while the marketing ethics employed by Sharia property entrepreneurs in Maros Regency generally adhere to Islamic business ethics, there are areas that require enhancement, such as trustworthiness, transparency, and accountability. Strengthening these aspects can contribute to fostering greater integrity and ethical conduct within the business community, aligning with the principles outlined in Islamic teachings.